Quantification of the dry history of the Martian soil inferred from in situ microscopy - Pike, W; Staufer, U; Hecht, M; Goetz, W; Parrat, D; Sykulska-Lawrence, H; Vijendran, S; Madsen, M (2011)
The particle size distribution (PSD) of a Martian soil sample, a useful indicator of the underlying soil formation processes, has been determined using optical and atomic-force microscopy data acquired by the Phoenix Mars lander. In particular, the presence and fraction of clay-sized particles in the PSD reflects the extent of aqueous interaction with the soil. Two size populations have been identified for the Martian sample: Larger, mostly rounded grains; and small reddish fines, notably with a very low mass proportion in the clay-size range below 2 μm. These fines reflect the smallest-scale formation processes, and indicate a single method of production for the particles up to 11 μm, a much larger value than that expected for the aqueous interaction of clay formation; this suggests the fines are predominantly the product of global aeolian weathering under very dry conditions. The proportion of clay-sized soils can be used to estimate that there has been much less than 5,000 years exposure to liquid water over the history of the soil. From the perspective of the PSD, lunar regolith, rather than terrestrial soil, is the best analog to Martian soil. A globally homogenous soil with such a PSD would be an unlikely habitat for the propagation of life on Mars. Copyright © 2011 by the American Geophysical Union.